Market Price and Income Elasticities of New Vehicle Demands - McCarthy, Patrick S. (The Review of Economics and Statistics, 1996)
Recent evidence from aggregate models of automobile demand indicates that, when not corrected for quality differences, market price elasticity of demand is substantially biased downwards. This note presents new information on market price and income elasticities derived from a disaggregate demand model that controls for cost, household income, vehicle attributes and perceived quality, consumer search, and manufacturer. Based on an extensive household survey of new vehicle purchasers in 1989, market price and income elasticities are estimated to be -0.87 and 1.70, respectively. Moreover, excluding vehicle quality from a well-specified model is found to have little effect upon the estimated market elasticities. Copyright 1996 by MIT Press.